An Ecumenical Commitment: Transforming Theological Education in Mission - Njoroge, Nyambura J. (International review of mission, 2005)
This paper is an attempt to demonstrate how the World Council of Churches had been involved in promoting and encouraging the transformation of theological education and ministerial formation as churches respond to changing landscape of theological reflection, mission, evangelism, diakonia and ecumenism in all six continents. The story begins with the concern expressed by the International Missionary Council at the Tambaram conference in 1938 that, “The weakest element in the entire enterprise of Christian Missions is theological education.” I take my cue from the parable of Jesus that new wine needs fresh wineskins. Transformation is a painstaking process and is usually met with a lot of resistance. Therefore, we need passionate, committed, bold and courageous individuals who are willing to provide leadership in situations where many might prefer the old skins for the new wine. I cite a few examples of how indeed new wine in theological education can be made as we respond to the challenges of the global HIV/AIDS pandemic, continuing violence, and listening to the voices of women and people with disabilities and other marginalized groups.